PENGARUH STRESS KERJA, KOMITMEN ORGANISASIONAL DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTION PERUSAHAAN OTOMOTIF - IRMA GUSTIANA ANDRIANI (Jurnal Bisnis dan Akuntansi, 2018)
The purpose of this study is to determine the effect of work stress, organizational commitment, and work satisfaction to turnover intention. The object of this research is a company operating in the field of car sales auto parts sales and maintenance of cars. The method used in this research is descriptive method and causality with multiple regression method to test the hypothesis. This research use nonprobability sampling technique with saturation sampling method. Respondents used in this study were 87 active employees. Technique of collecting data by using questionnaire..The result of the research shows that work stress has significant effect to turnover intention, but organizational commitment and work satisfaction has no significant effectto turnover intention.